Economywide impact of avian flu in Ghana: A dynamic CGE model analysis - Diao, Xinshen (International Food Policy Research Institute, 2009)
We use a dynamic CGE model to quantitatively assess the economywide impact of HPAI in Ghana. The likely effect of an avian flu outbreak is modeled as demand or supply shocks to the poultry sector. Our analysis shows that, while chicken is a quite small sector of the Ghanaian economy, the shock in chicken demand due to consumers' anxieties is the dominant factor in causing chicken production to fall. The indirect effect on soybean and maize that are used as chicken feed is also large. Under the worst-case scenario, soybean production will fall by 37 percent and maize by 6.4 percent. However, the economywide impact on both AgGDP and GDP is very small. In the worst-case scenario, in which chicken production falls by 70 percent in 2011, AgGDP falls by only 0.4 percent and GDP is almost unchanged. However, the livelihood impacts of a HPAI outbreak could be significant for some sections of the population in Ghana particularly those involved in the poultry sector. Micro-level analysis of chicken producers' livelihood, therefore, is necessary.